Early settlement and subsistence in the Casma Valley, Peru - Pozorski, Shelia Griffis (University of Iowa Press, 1987)
The Casma Valley of Peru's north central coast contains the largest New World structure of its time period--2500 to 200 BC--as well as one of the densest concentrations of early sites. In this detailed and thought-provoking volume, Sheila and Thomas Pozorski date each major early site, assess this important valley's diet and subsistence changes through time, and begin to reconstruct the development of Casma Valley society. Fifteen sites are surveyed, including Pampa de las Llamas-Moxeke, the earliest planned city in the New World. The Pozorskis then synthesize their own fieldwork and previous.